IMPLEMENTASI PEMBELAJARAN MENDALAM (DEEP LEARNING) DALAM KURIKULUM MERDEKA UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PAUD - Abdul Aziz; Tri Mulyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the deep learning approach within the Merdeka Curriculum to enhance pedagogical competence among early childhood education (PAUD) teachers. The background of this research is the limited application of meaningful and contextual learning practices in PAUD, where learning activities are often still teacher-centered and focused on memorization. The purpose of this study is to analyze the effectiveness of deep learning strategies in improving teachers’ pedagogical skills, particularly in planning, implementing, and evaluating learning activities. This research employed a qualitative descriptive method with data collected through observation, interviews, and documentation involving PAUD teachers. The results indicate that the application of deep learning encourages teachers to design learning activities that are more student-centered, contextual, and reflective of children’s developmental characteristics. Furthermore, teachers demonstrated improved abilities in facilitating active learning, fostering social-emotional development, and integrating real-life experiences into classroom activities. The study concludes that deep learning is a relevant and effective approach for strengthening pedagogical competence in PAUD when implemented consistently and supported by adequate professional development.